Association between tea consumption and frailty among Chinese older adults: A cross-sectional study - Li, Shaojie; Cui, Guanghui; Yin, Yongtian; Lv, Faqin; Yao, Yao (Frontiers in Nutrition, 2022)
Background: Chronic inflammation is considered one of the main mechanisms leading to frailty. It has been demonstrated that tea consumption reduces chronic inflammation. Few epidemiological studies have investigated the association between tea consumption and frailty. Objective: This study aimed to analyze the association between tea consumption and frailty in Chinese older adults. Methods: Between March and May 2021, we enrolled 2,144 older adults aged ≥60 years in Jinan City, Shandong Province, China, using multi-stage stratified cluster sampling. We assessed tea consumption and frailty in older adults using the Tilburg Frailty Indicator and the frequency of tea consumption, respectively. We applied multiple logistic regression analysis to examine the association between tea consumption and frailty, controlling for a set of potential covariates. Results: The prevalence of frailty among older Chinese adults was 38.3% (821/2144). Tea consumption was categorized as daily (30.4%), occasionally (20.9%), and rarely or never (48.7%). As indicated by the fully adjusted model, daily tea consumption was associated with a lower prevalence of frailty (OR=0.73, 95%CI=0.57-0.94). However, this association only applied to men, younger older adults aged 60-79 years, rural residents, and regular participants in community activities. In addition, we observed a linear relationship between tea consumption and the prevalence of frailty (P for trend = 0.017). Conclusions: Higher tea consumption was associated with a lower prevalence of frailty in older adults, especially those men, older adults aged 60-79, rural residents, and individuals who regularly participated in community activities. Further longitudinal and experimental studies are needed to determine the causation between tea consumption and frailty.